2022
DOI: 10.3390/nano12203695
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresistive Properties of Natural Hydraulic Lime Binary Pastes with Incorporated Carbon-Based Nanomaterials under Cyclic Compressive Loadings

Abstract: Natural Hydraulic Limes (NHL) are extensively used for the restoration of Monuments of Cultural Heritage, often combined with pozzolanic materials, such as natural pozzolans and metakaolin etc. In the present study, five (5) different cases of binary lime-based pastes composed of a specific type of NHL (NHL5) and metakaolin as pozzolanic addition were examined, that were reinforced with carbon nanostructures, namely graphene and carbon nanotubes. For the first time in restoration mortars, the incorporation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…[153,155] Further work from Dimou et al showed no significant changes in the flexural strength due to the addition of GO, but an improvement in the compressive strength, which was reported to increase by 20-30% compared with the reference mortar. [156][157][158] Besides investigating these properties, Dorin et al proved that GO addition only slightly improves the adhesion of the modified mortar. In these studies on the influence of GO on the performance of natural hydraulic mortars, different concentrations of GO in different physical forms (aqueous dispersions or powder) have been tested.…”
Section: Loss Of Structural Integritymentioning
confidence: 99%
See 2 more Smart Citations
“…[153,155] Further work from Dimou et al showed no significant changes in the flexural strength due to the addition of GO, but an improvement in the compressive strength, which was reported to increase by 20-30% compared with the reference mortar. [156][157][158] Besides investigating these properties, Dorin et al proved that GO addition only slightly improves the adhesion of the modified mortar. In these studies on the influence of GO on the performance of natural hydraulic mortars, different concentrations of GO in different physical forms (aqueous dispersions or powder) have been tested.…”
Section: Loss Of Structural Integritymentioning
confidence: 99%
“…[224] Beyond these applications as external sensors, GRMs could also be used as a sensing system within complex matrices such as cementitious materials. [225] A seminal work from Dimou et al [156] proposed a binary paste matrix (natural hydraulic lime and metakaolin) modified with rGO as reinforcement for the development of cultural heritage restoration mortars. The addition of rGO provokes a decrease in electrical resistance that indicates a good distribution of the electrically conductive nanomaterials within the binder, forming an efficient electrical network.…”
Section: Monitoring Technologies and Sensorsmentioning
confidence: 99%
See 1 more Smart Citation